THE EFFECT OF USING A THERMAL TERAHERTZ DEVICE PRIOR TO REHABILITATION EXERCISES ON REDUCING ELBOW JOINT PAIN AND IMPROVING RANGE OF MOTION IN ATHLETES WITH DISABILITIES (Proximus Journal of Sports Science and Physical Education, 2026)
Accordingly, the researcher conducted a case study by designing a rehabilitation program supported by modern modalities using a thermal terahertz device for athletes with disabilities suffering from elbow joint injuries. The significance of this research lies in establishing a rehabilitation protocol accompanied by a terahertz device for the injured limb, enabling the athlete to perform sport-specific activities related to this joint and to return rapidly to normal activity and achievement.